2002
DOI: 10.1080/01421590220134114
|View full text |Cite
|
Sign up to set email alerts
|

Student access and use of IT during general practice attachments

Abstract: As universities change the delivery of their medical undergraduate courses, many have started to develop the community as a learning resource. In Manchester, part of the rationale behind problem-based learning is that students become familiar with the tools for finding information. Within the medical school and its main teaching hospitals, students have access to varied information resources using IT. These are often less available from off-campus sites and particularly within general practice. Even where avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…There is a need to invest in the seasonal resources of books, journals, IT, video recorders and appropriate teaching equipment 13 . Students have commented that the main benefits of IT provision in the practice are as a tool for communication and a learning resource 14 …”
Section: Preparing the Ingredients Of The Menumentioning
confidence: 99%
See 3 more Smart Citations
“…There is a need to invest in the seasonal resources of books, journals, IT, video recorders and appropriate teaching equipment 13 . Students have commented that the main benefits of IT provision in the practice are as a tool for communication and a learning resource 14 …”
Section: Preparing the Ingredients Of The Menumentioning
confidence: 99%
“…A student consultation room allows students to see patients, consider what is wrong and what should be done, prepare, rehearse and present their findings 15 . Space constraints have been widely reported as an obstacle to quality community placements, and a need for revenue costs for teaching accommodation has been identified 3,12–14,16 …”
Section: Preparing the Ingredients Of The Menumentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7] Researchers at medical schools in the United States, Canada, and the United Kingdom have also reported that following the implementation of computer-based learning resources at the library and in clinical rotations, students both used these resources and thought they were a valuable addition. [8][9][10] The past work on electronic resources to teach clinical medicine suggests that students learn about the same amount of material from electronic resources as they do from print resources, but do so faster. Learners also seem to prefer the electronic resources.…”
mentioning
confidence: 99%